2022
DOI: 10.14254/jems.2022.7-1.4
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the determinants of environmentally-friendly apparel purchase intention in Indonesia: Incorporating environmental concern and knowledge into the theory of planned behavior

Abstract: The clothing industry is a high-growth industry that is attractive to be occupied by the business. However, behind its appeal, this industry brings harmful impacts to the environment. The fashion industry is considered the 2nd most destructive industry in the world. Environmental damage due to industry occurs not only in the production process but also in consumption and disposal. As the growth of this industry cannot be separated from consumer intervention, efforts to improve the environmental impact caused b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 69 publications
2
10
2
2
Order By: Relevance
“…This study provides evidence that functional value has a positive influence on continued usage intentions toward FDAs in the post-COVID-19 outbreak ( H1 ). This result further supports prior studies of Rizkalla and Setiadi (2020) and Tandon et al (2021). This shows the significance of factors, such as offered benefits, convenience or various menus, reasonable price and consumers’ evaluation of whether the purchase is valuable for money in respect of cost–quality.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study provides evidence that functional value has a positive influence on continued usage intentions toward FDAs in the post-COVID-19 outbreak ( H1 ). This result further supports prior studies of Rizkalla and Setiadi (2020) and Tandon et al (2021). This shows the significance of factors, such as offered benefits, convenience or various menus, reasonable price and consumers’ evaluation of whether the purchase is valuable for money in respect of cost–quality.…”
Section: Discussionsupporting
confidence: 88%
“…Consumers’ rational buying behaviors and preferred products are primarily influenced by price, quality and value (Candan et al , 2013). According to utility theory, when consumers make a purchase decision, they always try to maximize their purchase utility, which is derived from the comparison between the benefit of the product and the cost incurred (Rizkalla and Setiadi, 2020). In the context of FDAs, functional value defined as the benefits and value for money, which FDA consumes perceived that they can ordering food at a reasonable price.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hanzaee & Taghipourian (2012) states that there is a positive influence of value for money on purchase intention. Likewise, past research also found that previous consumers' perceptions regarding the value of the product can affect consumer desire to buy and become a trigger for buying interest (Kittikowit et al, 2018;Rizkalla & Setiadi, 2020). Based on these postulations, the following hypothesis is formed: H4: Value for money has a positive influence towards the purchase intention of organic menstrual cup…”
Section: Value For Moneymentioning
confidence: 91%
“…The health and safety aspects, low maintenance cost and better quality of green products are the main factors encouraging the green consumption pattern among Sri Lankan consumers. The consumers in developing countries prefer ecofriendly products by analysing the degree of fulfilment of consumer needs and consumption value [71]. Moreover, the consumer perception of product safety and environmental impact induces people from developing countries to follow a sustainable consumption pattern.…”
Section: Case Study On Sustainable Consumer Behaviour In Developing C...mentioning
confidence: 99%